2015
DOI: 10.1007/s11144-015-0933-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a new cobalt hydrazone complex and its catalytic activity in the hydrogenation of carbon monoxide (Fischer–Tropsch synthesis)

Abstract: A new hydrazone ligand, 4-methoxyacetophenone benzoyl hydrazone and its cobalt complex were synthesized and characterized using elemental analysis, Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, 1 H NMR spectral data, and powder X-ray diffraction techniques. Moreover, the thermal gravimetric analysis and electrochemical (cyclic voltammetry) properties of the ligand and its complex were investigated. The catalytic ability of the Co-MABH complex as a new metal-organic catalyst in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…(iv) The catalytic activity of synthetic catalysts is morphology dependent. As mentioned in the previous section, the preparation of catalysts through thermolysis of Cu complex lead to creating some features such as high active phase dispersion, small particle size and high specific surface area 74–76 . By increasing the specific surface area of a catalyst, more active sites will be available for adsorption of MB and followed by degradation of dye, enhancing the photodegradation of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…(iv) The catalytic activity of synthetic catalysts is morphology dependent. As mentioned in the previous section, the preparation of catalysts through thermolysis of Cu complex lead to creating some features such as high active phase dispersion, small particle size and high specific surface area 74–76 . By increasing the specific surface area of a catalyst, more active sites will be available for adsorption of MB and followed by degradation of dye, enhancing the photodegradation of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation method plays an important role in the performance and activity of the catalysts, because it can affect the physicochemical properties of the catalysts. As mentioned in the previous section, the preparation of Co 3 O 4 -uc and Co 3 O 4 -hc through thermolysis of dinuclear inorganic complex lead to creating some features such as high active phase dispersion, small particle size and high specific surface area [38,39]. However, adsorption efficiency can be affected by several parameters such as particles size, BET surface area, and crystalline phase.…”
Section: Sorbent Dose (G/l)mentioning
confidence: 99%
“…The results of their studies have shown that nanoparticles prepared by thermal decomposition of the inorganic complex have higher catalytic performance than the catalysts which prepared by other methods, such as impregnation and co-precipitation. The use of the inorganic complex as precursor for the preparation of nanoparticles potentially provides many advantages as a new route since: (a) the nanoparticles which obtained by thermolysis of inorganic complexes have high catalytic performance due to thier high surface area and small particle size [38,39], (b) the intimate metal contact in the synthesized complexes causes their homogeneous dispersion in the catalyst structure [40]. In this study, for the first time, an effective Co 3 O 4 nanosorbent was prepared by the thermal decomposition of a binuclear inorganic complex through the following steps.…”
Section: Introductionmentioning
confidence: 99%